2010
DOI: 10.1007/s10911-010-9173-1
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition (EMT) in Tumor-Initiating Cells and Its Clinical Implications in Breast Cancer

Abstract: There is increasing support for the hypothesis that most tumors contain a subpopulation of cells, referred to here as tumor initiating cells (TICs), with the ability to self-renew and to regenerate all the cell types within the tumor. TICs are enriched in breast cancer patients after common treatments, indicating their intrinsic therapeutic resistance. Two independently-derived gene transcription "signatures" of TICs from different studies indicate enrichment of TICs within the recently-identified "claudin-low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
192
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(195 citation statements)
references
References 43 publications
2
192
0
1
Order By: Relevance
“…Most importantly, cancer stem cells (CSCs) derived from human breast cancer specimens are enriched for EMT markers (23). These and other similar observations (25) suggested that the EMT and CSC programs are intertwined and that acquisition of EMT traits by cancer cells is sufficient to bestow on them CSC characteristics. Because LOX was a critical regulator of EMT, we asked whether it played similar roles in regulating the CSC program in BCCs.…”
Section: Lox Does Not Mediate the Msc-induced Expansion Of Cancer Stemmentioning
confidence: 74%
“…Most importantly, cancer stem cells (CSCs) derived from human breast cancer specimens are enriched for EMT markers (23). These and other similar observations (25) suggested that the EMT and CSC programs are intertwined and that acquisition of EMT traits by cancer cells is sufficient to bestow on them CSC characteristics. Because LOX was a critical regulator of EMT, we asked whether it played similar roles in regulating the CSC program in BCCs.…”
Section: Lox Does Not Mediate the Msc-induced Expansion Of Cancer Stemmentioning
confidence: 74%
“…Claudin-2 and breast cancer liver metastasis S Tabariès et al by features of an epithelial-to-mesenchymal transition, enhanced stem cell characteristics and resistance to chemotherapy (Creighton et al, 2009(Creighton et al, , 2010Hennessy et al, 2009;Prat et al, 2010;Taube et al, 2010). At the present time, the status of claudin-2 expression within these 'claudin-low' tumors has not been described.…”
Section: Discussionmentioning
confidence: 89%
“…The epithelial mesenchymal transition (EMT) is an essential component of tumor progression and also plays a normal role in embryonic development, tissue remodeling and wound repair [1] . The occurrence of the EMT during tumor progression allows benign tumor cells to acquire three major changes in cellular phenotype.…”
Section: Introductionmentioning
confidence: 99%